Does pomegranate extract supplementation improve the clinical symptoms of patients with allergic asthma? A double-blind, randomized, placebo-controlled trial - Hosseini, Seyed Ahmad; Shateri, Zainab; Abolnezhadian, Farhad; Maraghi, Elham; Haddadzadeh Shoushtari, Maryam; Zilaee, Marzie (Frontiers in Pharmacology, 2023)
Background: Asthma essentially represents a chronic inflammatory disease that manifests as a lifelong condition with different severity throughout the life of patients with asthma. Pomegranate holds three times the antioxidant activity compared to other polyphenol-rich food sources like green tea, which may positively impact asthma. Aim of the study: This research aimed to investigate the pomegranate supplementation influences clinical symptoms, eosinophil, basophil, and neutrophil counts in patients with allergic asthma. Materials and Methods: Participants (n = 64) suffering from mild to moderate allergic asthma were randomly divided into two groups: The control group received placebo capsules and the intervention group received 250 mg pomegranate extract capsules twice a day (for 8 weeks). To analyze the data, we used SPSS software (version 22). The significance level of p-value was considered less than 0.05. Results: The findings showed that the pomegranate extract improved patients’ clinical symptoms like daily breath shortness, nocturnal breath shortness, and limitation of asthma-related activity in the intervention group compared to the control group. Furthermore, eosinophil, basophil, and neutrophil counts were significantly decreased in the intervention group. Also, by comparing the two groups, the levels of change in neutrophils and eosinophils were statistically significant. Conclusion: It appears that the pomegranate extract can ameliorate some clinical symptoms and reduce neutrophils, basophils, and eosinophils in allergic asthma patients. Clinical Trial Registration:https://www.irct.ir/trial/45612; identifier: IRCT20200205046384N1.